Penegakan Hukum Pada Kasus Investasi Ilegal Daring Ditinjau dari Aspek Restorative Justice - Putri, Nirwana; Adlia Nur Zhafarina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Achmad Yani Yogyakarta, 2023)
Illegal online investments have become a serious issue in the modern financial world, affecting communities and causing financial instability. This study examines the restorative justice approach in law enforcement against perpetrators of illegal online investments, with a focus on empowering victims, rehabilitating wrongdoers, and recovering losses incurred by these illicit investment schemes using normative legal research methods. The research findings demonstrate that the restorative justice approach can provide more effective solutions to address illegal online investments. By empowering victims, they can actively participate in the law enforcement process, gaining a better understanding of fraudulent schemes and how to prevent them in the future. Second, rehabilitating wrongdoers becomes a crucial component of restorative justice. By identifying the causes and factors that drive individuals to engage in illegal online investment schemes, the legal system can offer opportunities for them to learn from their mistakes, change their behavior, and undergo rehabilitation. This can help reduce the risk of these individuals getting involved in illegal activities again in the future. Third, within the context of restorative justice, compensation and restitution take center stage. Material and moral restitution to victims can restore a sense of justice and rebuild public trust in the legal system. The restorative justice approach in enforcing the law against illegal online investment perpetrators offers solutions centered around recovery, victim empowerment, wrongdoer rehabilitation, and compensation for victims. In the effort to combat illegal online investments, restorative justice can serve as an effective tool to bring about justice and rectify the losses caused by these unlawful practices. This can be achieved through collaboration between the government, financial institutions, and the community. Thus, the restorative justice approach can make a significant contribution to the fight against illegal online investments and create a safer and fairer financial environment.